A Novel Hybrid Particle Swarm- Multiverse Optimization based Voltage Stability Improvement in IEEE 57 Bus System - K.Dhal, P; Ramash Kumar, K (International Journal of Engineering and Technology, 2018)
The major role of power system is voltage stability. It is required to plan properly and smooth operation and control. It presents a new approach of voltage stability improvement in IEEE 57 bus system using hybrid algorithm. The hybrid algorithm (PSO-MVO) is combination of PSO which is used for exploitation and MVO used for exploration. It is used in an uncertain environment. The FACTS device as STATCOM is connected in IEEE 57 test system to check for event of voltage stability improvement through power system analysis tool (PSAT) software. Once the ability of system goes through sudden loading, its stability gets affected. It desires compensation to boost voltage from disturbances. The varied operative condition while not used STATCOM in the system, used with STATCOM tuned by PSO-MVO algorithm are measured judge the performance of the projected system. The hybrid PSO-MVO technique is implemented in this paper to solve the proposed problem. The simulation results are obtained by PSAT software for 57 IEEE bus systems. The hybrid algorithm validates its effectiveness compare to individual PSO and MVO algorithm. Â Â Â Â